Peta Strategi Bisnis Mengunakan Metode Strength Weakness Opportunity Threats (SWOT) Dan Metode Balance Score Card: Studi Kasus Toko Gantar Plastik - Iyat Ratna Komala (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Information systems strategic planning must support the business strategy planning of an organization. This is done so that the organization's business goals are achieved. Therefore, this research aims to create a business strategy map at the Gantar Plastik Store based on vision, mission, strategic targets, key performance indicators (KPI), environmental analysis within and outside the organization using the Strength Weakness Opportunity Threat (SWOT) method and making a map. strategy using the Balance Score Card (BSC) method. Based on the analysis and results of the SWOT method calculations that have been carried out, a proposal is obtained, namely an aggressive strategy, because the resulting values for IFE = 0.39 and EFE = 0.56. So, based on the results of the calculations and visualization of the diagram, the Gantar Plastik Shop is proposed to take aggressive strategic steps, meaning that the shop must expand because the strengths and opportunities are large while the threats and weaknesses are small. The next method used is the Balance Score Card method, this method has 4 perspectives, namely Learning and Growth, Internal Process, Customer and Financial. So that the proposed strategy map is given precisely, according to the target, with detailed targets and specific improvement proposals.